2018
DOI: 10.1111/1365-2435.13140
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic and deterministic effects on interactions between canopy and recruiting species in forest communities

Abstract: Interactions between established (canopy) and recruiting individuals (recruits) are pervasive in plant communities. Studies on recruitment in forests have mainly focused on negative density‐dependent conspecific interactions, while the outcomes of heterospecific canopy–recruit interactions have received much less attention and are generally assumed to be driven by stochastic processes. Herein, we explore the relative influence of stochastic (abundance) and deterministic (species identity and phylogenetic dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 67 publications
5
36
0
1
Order By: Relevance
“…In the communities studied by Valiente-Banuet (2011), Marcilio-Silva et al (2015) and Alcántara, Pulgar, Trøjelsgaard, Garrido, and Rey (2018), the frequency of canopy-recruit interactions was positively related with the abundance of the interacting species, so the prevalence of unobserved interactions could be a consequence of the low abundance of many species which may severely limit their chances of interacting (i.e., they are "neutral forbidden" interactions as defined by Canard et al, 2012). However, Alcántara et al (2018) found that nearly 1/3 of the unobserved interactions were consistently unobserved even though the participating species were abundant enough to interact at least by chance, what indicates that an important part of the potential interactions are impeded for some ecological reason (i.e., they are "forbidden links" as defined by Olesen et al, 2011). Among the realized interactions, interspecific interactions had more frequently neutral or enhancing than depressing effects on recruitment, while intraspecific interactions had more frequently depressing effects (but some intraspecific enhancing effects were also found).…”
Section: What Do We Know About Rns?mentioning
confidence: 95%
See 4 more Smart Citations
“…In the communities studied by Valiente-Banuet (2011), Marcilio-Silva et al (2015) and Alcántara, Pulgar, Trøjelsgaard, Garrido, and Rey (2018), the frequency of canopy-recruit interactions was positively related with the abundance of the interacting species, so the prevalence of unobserved interactions could be a consequence of the low abundance of many species which may severely limit their chances of interacting (i.e., they are "neutral forbidden" interactions as defined by Canard et al, 2012). However, Alcántara et al (2018) found that nearly 1/3 of the unobserved interactions were consistently unobserved even though the participating species were abundant enough to interact at least by chance, what indicates that an important part of the potential interactions are impeded for some ecological reason (i.e., they are "forbidden links" as defined by Olesen et al, 2011). Among the realized interactions, interspecific interactions had more frequently neutral or enhancing than depressing effects on recruitment, while intraspecific interactions had more frequently depressing effects (but some intraspecific enhancing effects were also found).…”
Section: What Do We Know About Rns?mentioning
confidence: 95%
“…These patterns may have discouraged the study of FNs in plant communities from many temperate and tropical environments. However, as argued above, the recruitment of one species can be facilitated by some species, depressed by others, and unaffected by others in any community (Alcántara et al, 2018). Moreover, the predominance of one type of interaction in some ecosystems must not lead to uncritically assume that all recruitment associations between plants have the same outcome.…”
Section: Focus On Facilitationmentioning
confidence: 97%
See 3 more Smart Citations